Surrealism : in the Tate Gallery Collection. - Tate Gallery, Liverpool (Liverpool : Tate Gallery, 1988)
Jean, Marcel ; Breton, André ; Arp, Jean ; Bellmer, Hans ; Calder, Alexander ; De Chirico, Giorgio ; Colquhoun, Ithell ; Dali, Salvador ; Delvaux, Paul ; Eluard, Paul ; Ernst, Max ; etc.
Surrealism in the Tate Gallery Collection, Tate Gallery, Liverpool, 24 May 1988 - 4 March 1989
boek